Completion of the Chloroplast Genomes of Five Chinese Juglans and Their Contribution to Chloroplast Phylogeny - Hu, Yiheng; Woeste, Keith E.; Zhao, Peng (Frontiers in Plant Science, 2017)
Juglans L. (walnuts and butternuts) is an economically and ecologically important genus in the family Juglandaceae. All Juglans are important nut and timber trees. Juglans regia (Common walnut), J. sigillata (Iron walnut), J. cathayensis (Chinese walnut), J. hopeiensis (Ma walnut), and J. mandshurica (Manchurian walnut) are native to or naturalized in China. A strongly supported phylogeny of these five species is not available due to a lack of informative molecular markers. We compared complete chloroplast genomes and determined the phylogenetic relationships among the five Chinese Juglans using IIumina sequencing. The plastid genomes ranged from 159,714 to 160,367 bp encoding 128 functional genes, including 88 protein-coding genes and 40 tRNA genes each. A complete map of the variability across the genomes of the five Juglans species was produced that included single nucleotide variants, indels (insertions and deletions), and large structural variants, as well as differences in simple sequence repeats (SSR) and repeat sequences. Molecular phylogeny strongly supported division of the five walnut species into two previously recognized sections (Juglans/Dioscaryon and Cardiocaryon) with a 100 % bootstrap (BS) value using the complete cp genomes, protein coding sequences (CDS), and the introns and spacers (IGS) data. The availability of these genomes will provide genetic information for identifying species and hybrids, taxonomy, phylogeny, and evolution in Juglans, and also provide insight into utilization of Juglans plants.